The Effect Of Profitability, Solvability, And Liquidity On Stock Prices Before And During The Covid-19 Pandemic - Dc, Achmad Furqaan; Darmansyah, Asep (Journal Of Social Science (JoSS), 2023)
This research aims to determine the effect of profitability, solvency, and liquidity on stock prices. Profitability in this research is proxied by the return on assets (ROA) and return on equity (ROE) ratio, solvency is proxied by the debt to asset ratio (DAR) and debt to equity ratio (DER), and liquidity is proxied by the cash ratio (CR), quick ratio (QR) and cash ratio. The type of research used in this research is quantitative research using multiple linear regression analysis and the Wilcoxon Signed Ranks Test. The results of this research show that return on assets does not affect stock prices before and during the Covid-19 pandemic. return on equity influences stock prices before and during the Covid-19 pandemic. The debt-to-asset ratio does not affect stock prices before and during the Covid-19 pandemic. Debt to Equity Ratio influences stock prices before and during the Covid-19 pandemic. The current ratio influences share prices before and during the Covid-19 pandemic. The quick ratio did not affect stock prices before and during the COVID-19 pandemic. The cash ratio did not affect share prices before and during the Covid-19 pandemic. Return on Assets (ROA), Return on Equity (ROE), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Cash Ratio (CR), Quick Ratio (QR), and Cash Ratio together affect stock prices before and during the covid-19 pandemic.